Custos ocultos estruturais: um estudo no âmbito do setor agroindustrial da cachaça do estado da Paraíba - Silva, Derik Harisson Leite da (2018)
Structural hidden costs are undetected costs in accounting records and managerial reports, arising from dysfunctions of the company's physical structure, which affect the profitability of organizations. In this sense, this research, carried out in the form of a case study, had the objective of identifying and measuring the hidden structural costs in the cachaça production process in a sugar mill, located in the Brejo micro region of Paraíba. For this purpose, a semistructured interview was conducted, aimed at the owner, aiming at obtaining information about the costing method used and the dysfunctions that arise from productive activities. At the same time, an on-site observation was made, which attempted to map all stages of cachaça production and to certify the responses obtained through the application of the interview. In a third moment, data on product costs were collected in the financial reports and managements for the 2016/2017 harvest period. This last methodological step served to feed the measurement data of the nine variables selected structural hidden costs, namely: absenteeism, work accident, idleness, stocks, inefficiencies, product quality, obsolescence, waste and missed opportunity. The production process was divided into: milling, fermentation, distillation and bottling. It was verified, through the application of the interview to the owner, that the company does not use any formal system to calculate costs. Among the structural hidden cost variables studied, three of them were not found: work accident, idleness and stocks. The recurring measurable hidden cost in all productive phases is absenteeism. In addition, the costs of waste and inefficiency were measured. Regarding the qualitative analysis, the observation process explained the dysfunctions present in the milling and fermentation stages related to the final quality of the beverage. Dysfunctions have also been identified that cause hidden costs of obsolescence and waste. The results of this research could, in summary, certify the occurrence of hidden structural costs in a medium sized enterprise, revealing that in organizations with outdated and inadequate administrative processes the managerial information of an in-depth analysis bring possibilities of improvement.